Pengaruh Biofeedback terhadap Program Peningkatan Kekuatan Otot - Romadhon, Aditya Johan; Nugroho, Fendy; Pajar Haryatno (Jurnal Fisioterapi Terapan Indonesia, 2025)
Background: In sport the muscle fiber composition surely affect athlete performances, selective training technic and using advance technology may improve and set a new standards for athlete optimal performances, technology innovation such as computer simulator has been use to generate realistic match simulation in several sport, but the technology is not cheap that many sport clubs can afford, so biofeedback may become innovation to improve athletes performance by monitoring muscle activation to achieve selective muscle contraction in muscle strengthening programs. Objective: The objective of this study was to evaluate whether auditory feedback as biofeedback can improve muscle activation in a strengthening program. Method: Biofeedback with an auditory feedback electrode placed on the pectoralis muscle pars sternum of 25 subjects in the experimental Group, while they performed a strengthening program and 25 subjects only performed the strengthening program using biofeedback without auditory feedback as controls. The strengthening program was taken for 2 sessions a week for 4 weeks. Result: The collected data showed a mean difference value for the experimental Group was 34.1 ± 14.23 µV and for the control Group was 4.24 ± 12.61 µV, only the experimental Group had a signification value p<0.05. Conclusion: Biofeedback combined with a muscle-strengthening program results in greater muscle activation.